Efek Jangka Pendek Pergerakan Jumlah Pesawat, Penumpang, dan Kargo Udara terhadap PDRB Subsektor Angkutan Udara di Sulawesi Barat (2014–2024): Analisis ARDL - Nur Ilmi Hasbah; Ana Uluwiyah (WARTA ARDHIA, 2025)
This study aims to analyze the influence of the aircraft movements, passenger numbers, and the air freight volume on the Gross Regional Domestic Product (GRDP) of the air transport subsector in Sulawesi Barat. The study uses quarterly data from Q1 2014 to Q4 2024 (44 observations) and applies the ARDL (3,4,0,0) model selected based on the Akaike Information Criterion (AIC). Stationarity and long-run relationships were tested using the Augmented Dickey-Fuller and Bounds tests, respectively, with no control variables included. The results indicate that only short-run effects were found, while no evidence of long-run cointegration exists among the variables. In the short run, aircraft movements have a positive and statistically significant association with the GRDP of the air transport subsector, whereas passenger numbers and the air freight volume show no significant relationship. However, the model’s high adjusted R² and absence of robustness checks suggest caution in interpretation, as omitted variable bias and limited causal inference may exist. These findings suggest that enhancing aircraft operations and connectivity could support short-term growth in the regional air transport subsector. However, further research incorporating structural breaks and robustness analyses is recommended to strengthen policy conclusions. These insights are relevant for policymakers seeking evidence-based strategies to improve regional air connectivity and optimize the economic role of the air transport subsector in Sulawesi Barat.